Factors in an Effort to Acquire the Efficiency of the Cargo Compartment Design on Tankers - Ardi Nugroho Yulianto; Teguh Putranto; Hasanudin Hasanudin; Abdullah Taufiq Akbar Siregar; Muhammad Ikbal Normawan; Raybonda Reinaldi Winarko; Adrian Rahmanto Putra; Noor Virliantarto; Good Year Surya Nusantara (Department of Ocean Engineering, 2024)
Tankers are one of the popular modes of transportation associated with liquid cargo. Efficiency with respect to the volume of cargo transported by tankers is an essential consideration in the transportation business process, especially fuel oil, which has become a benchmark for the global economy recently. Various studies have been carried out to optimize cargo space. This study aims to define the factors that influence cargo compartment efficiency to increase the effectiveness in the transportation business. In this study, it is known that the transverse bulkhead arrangement affects the payload capacity, which is related to the criteria in the naval architect principle. The hopper design also influences the optimization of cargo volume, which can provide benefits in terms of payload. Excess cargo volume on existing ships due to hopper design optimization, the future ship design can reduce the length of the cargo compartments that still meet the desired payload. Reducing the length of the cargo hold will undoubtedly provide an opportunity to optimize the scantling analysis for longitudinal and transverse ship structures. This study is expected to be a reference and a more detailed discussion regarding the efficiency of cargo space on tankers in the future.